Novel Magnetic Nanohybrids: From Iron Oxide to Iron Carbide Nanoparticles Grown on Nanodiamonds - Panagiotis Ziogas; Athanasios B. Bourlinos; Jiri Tucek; Ondrej Malina; Alexios P. Douvalis (Magnetochemistry, 2020)
The synthesis and characterization of a new line of magnetic hybrid nanostructured materials composed of spinel-type iron oxide to iron carbide nanoparticles grown on nanodiamond nanotemplates is reported in this study. The realization of these nanohybrid structures is achieved through thermal processing under vacuum at different annealing temperatures of a chemical precursor, in which very fine maghemite (γ-Fe2O3) nanoparticles seeds were developed on the surface of the nanodiamond nanotemplates. It is seen that low annealing temperatures induce the growth of the maghemite nanoparticle seeds to fine dispersed spinel-type non-stoichiometric ~5 nm magnetite (Fe3−xO4) nanoparticles, while intermediate annealing temperatures lead to the formation of single phase ~10 nm cementite (Fe3C) iron carbide nanoparticles. Higher annealing temperatures produce a mixture of larger Fe3C and Fe5C2 iron carbides, triggering simultaneously the growth of large-sized carbon nanotubes partially filled with these carbides. The magnetic features of the synthesized hybrid nanomaterials reveal the properties of their bearing magnetic phases, which span from superparamagnetic to soft and hard ferromagnetic and reflect the intrinsic magnetic properties of the containing phases, as well as their size and interconnection, dictated by the morphology and nature of the nanodiamond nanotemplates. These nanohybrids are proposed as potential candidates for important technological applications in nano-biomedicine and catalysis, while their synthetic route could be further tuned for development of new magnetic nanohybrid materials.